Exploring the oncogenic role and prognostic value of CKS1B in human lung adenocarcinoma and squamous cell carcinoma - Hossain, Md. Solayman; Islam Tusar, Tariqul; Faruqui, Nairita Ahsan; Rahaman, Tanjim Ishraq; Sharker, Yasin Arafath; Santo, Shimran Saharia; Moin, Abu Tayab; Araf, Yusha; Afif, Ibrahim Khalil; Saikat, Shoaib; Hosen, Mohammad Jakir (Frontiers in Genetics, 2025)
IntroductionLung cancer (LC) is a highly aggressive malignancy and remains a leading cause of cancer-related mortality worldwide. Non-small cell lung cancer (NSCLC), which includes adenocarcinoma (LUAD) and squamous cell carcinoma (LUSC), accounts for the majority of these deaths. Due to the lack of early clinical symptoms and late-stage diagnosis, there is an urgent need for precise and targeted therapeutic strategies. Cyclin-dependent kinase regulatory subunit 1B (CKS1B), a key regulator of the cell cycle, has been implicated in various human cancers. Emerging evidence suggests that its upregulation is associated with poor prognosis in NSCLC, highlighting its potential as a biomarker for early detection and targeted therapy.MethodsIn this study, we conducted a comprehensive bioinformatics analysis to evaluate the role of CKS1B in LUAD and LUSC. Differential gene expression analysis, survival analysis, immune infiltration correlation, and pathway enrichment analysis were performed using publicly available transcriptomic datasets. Additionally, gene interaction networks were analyzed to assess the functional significance of CKS1B in lung cancer progression.ResultsOur findings indicate a significant overexpression of CKS1B in LUAD and LUSC compared to normal lung tissues. Survival analysis demonstrated that higher CKS1B expression correlates with poor prognosis in NSCLC patients. Immune infiltration analysis revealed a potential role of CKS1B in modulating the tumor microenvironment, further supporting its relevance in lung cancer progression. Functional enrichment analysis highlighted its involvement in critical oncogenic pathways, including cell cycle regulation and immune modulation.DiscussionThe results suggest that CKS1B serves as a potential biomarker for early detection and prognosis in NSCLC. Its association with immune response pathways underscores its possible role in immunotherapy. However, despite these promising findings, further in vivo and in vitro studies are necessary to validate CKS1B's clinical applicability as a diagnostic and therapeutic target for lung cancer.